Molecular Study of 16SrRNA Gene in Enterobacteriaceae isolated from Iraqi Patients - Mahmood, Shahad Hisham; Turkey, Ahmed Mohamed; Khalaf, Ilham Abdul Hadi (Al-Nahrain Journal of Science, 2018)
This study included the collection of 204 clinical and non-clinical samples from Ibn-Al-Baladi childbirth Hospital, Al-Yarmouk Teaching Hospital and Imam Ali Hospital in Baghdad, from both genders of different ages. The collected samples were distributed according to the collection source (urine, wounds, burns, feces, Tigris River water in Baghdad and soil samples). A total of isolates of Escherichia coli (48.43 %), 15 isolates Klebsiella pneumoniae (23.43 %), 10 isolates of Enterobacter cloacae (15.62 %) and 8 isolates of proteus mirabilis (12.50 %) were isolated and identified based on microscopic culture, conventional methods, VITEK 2 and molecular identification of 16 SrRNA gene. Our investigations indicated that Escherichia coli and Klebsiella pneumoniae species represent the most frequent isolates, whereas both Enterobacter cloacae and Proteus mirabilis were the less frequent species. The results of the analysis of the sequencing of selected 21 isolates were deposited in the National Center for Biotechnology Information (NCBI) belong to the four species (From LC314477.1 to LC314497.1).